2017
DOI: 10.1039/c7ja00273d
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous speciation of chromate, arsenate, molybdate and vanadate in alkaline samples by HPLC-ICP-MS at different concentration levels of vanadate

Abstract: Flay ash, cement and electric arc furnace (EAF) dust are frequently mixed in building composites. From them, chromium (Cr), arsenic (As), molybdenum (Mo) and vanadium (V) may be leached. Concentrations of V in leachates may be significantly higher than those of Cr, As and Mo, making simultaneous speciation analysis particularly difficult. In this work, a high performance liquid chromatography inductively coupled plasma mass spectrometry (HPLC-ICP-MS) procedure was used for simultaneous speciation of chromate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…When U-rich particles had been located, LA-ICP-MS was used for IRA. The determined 235 U/ 238 38 to be reliable, accurate (spike recoveries in the range 98-102%), precise (repeatability <3%) and fast (chromatographic separations in 10 minutes).…”
Section: Inductively Coupled Plasma Mass Spectrometrymentioning
confidence: 92%
See 4 more Smart Citations
“…When U-rich particles had been located, LA-ICP-MS was used for IRA. The determined 235 U/ 238 38 to be reliable, accurate (spike recoveries in the range 98-102%), precise (repeatability <3%) and fast (chromatographic separations in 10 minutes).…”
Section: Inductively Coupled Plasma Mass Spectrometrymentioning
confidence: 92%
“…Ellis et al 274 were able to analyse a single sanidine grain by splitting large crystals into up to four fragments. One split was used to perform high-precision 40 A recent study demonstrated 276 that cosmogenic 38 Ar exposure dating of Ca-rich minerals could be a valuable new dating tool and provided the first terrestrial cosmochrons using the 38 Ar isotope system. Previous application of this dating technique to terrestrial samples had been considered impracticable because of the high atmospheric 38 Ar background on Earth.…”
Section: X-ray Spectrometrymentioning
confidence: 99%
See 3 more Smart Citations